Penilaian Kualitas Permukaan Jalan dengan Penggunaan Pavement Condition Index (PCI) di Jalan Adiwerna II, Kabupaten Tegal - Marwanto, Riza Phahlevi; Azel Rizal Jovian; Hadi, Suprapto (Pusat riset dan Inovasi Nasional, 2024)
This study evaluates the pavement condition of 3,300 meters of Adiwerna Highway II using the Pavement Condition Index (PCI) method based on the ASTM D6433-18 standard. The road is divided into 18 segments to facilitate analysis, with data obtained through visual surveys. The results show five main types of damage, dominated by patches (84%). PCI values ​​range from 38–86 with an average of 69 (